2020
DOI: 10.3390/mi11110953
|View full text |Cite
|
Sign up to set email alerts
|

Xenon Flash Lamp Lift-Off Technology without Laser for Flexible Electronics

Abstract: This study experimentally investigated process mechanisms and characteristics of newly developed xenon flash lamp lift-off (XF-LO) technology, a novel thin film lift-off method using a light to heat conversion layer (LTHC) and a xenon flash lamp (XFL). XF-LO technology was used to lift-off polyimide (PI) films of 8.68–19.6 μm thickness. When XFL energy irradiated to the LTHC was 2.61 J/cm2, the PI film was completely released from the carrier substrate. However, as the energy intensity of the XFL increased, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Overall, these results demonstrate that the PLO process can aid in fabricating lightweight, ultrathin (<20 μm) solar cells that could be attractive for space and stratospheric applications. Further, this process, as demonstrated, also enables monolithic device fabrication on the top of polymeric films, not requiring transferring the completed devices to foreign substrates after lift-off, which is a typical step in other lift-off mechanisms. …”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Overall, these results demonstrate that the PLO process can aid in fabricating lightweight, ultrathin (<20 μm) solar cells that could be attractive for space and stratospheric applications. Further, this process, as demonstrated, also enables monolithic device fabrication on the top of polymeric films, not requiring transferring the completed devices to foreign substrates after lift-off, which is a typical step in other lift-off mechanisms. …”
Section: Resultsmentioning
confidence: 98%
“…The temperature at the LAL–PI interface greatly exceeds this during the PLO process, resulting in the release of the PI film and device layer. In this way, PLO is fundamentally similar to the laser lift-off process but with the advantage of large-area illumination…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cured PI films on the LTHC carrier glass were placed on the stage and then triggered by XFL pulses. The applied XFL Energy was fixed at a pulse height of 500 V, and the exposure time was varied from 1–7 ms [ 17 ]. The thicknesses of released films were 12 μm.…”
Section: Methodsmentioning
confidence: 99%
“…Bian et al [ 10 ] reported that lowering the excimer laser fluence and increasing the number of scans reduces the thickness of polyimide film during the LLO process. Lee et al [ 17 ] reported a new lift-off process using a Xe Flash lamp power source and a specially developed light-to-heat conversion (LTHC) layer. At this time, no studies have reported the investigations of differently structured polymer substrates in the new lift-off process.…”
Section: Introductionmentioning
confidence: 99%